∫ f(x) dx = sinx/x,f(x) = (x cosx - sinx)/x²
∫ x f'(x) dx
= ∫ x df(x)
= x f(x) - ∫ f(x) dx
= x * (x cosx - sinx)/x² - sinx/x + C
= cosx - (sinx)/x - (sinx)/x + C
= cosx - (2sinx)/x + C
-------------------------------------------------------------------------------
∫ (1 - lnx)/(x - lnx)² dx
= ∫ [(x - lnx) + (1 - x)]/(x - lnx)² dx
= ∫ dx/(x - lnx) + ∫ (1 - x)/(x - lnx)² dx
= x/(x - lnx) - ∫ x * (1 - 1/x)/(x - lnx)² dx + ∫ (1 - x)/(x - lnx)² dx
= x/(x - lnx) - ∫ (x - 1)/(x - lnx)² dx + ∫ (1 - x)/(x - lnx)² dx
= x/(x - lnx) + ∫ (1 - x)/(x - lnx)² dx + ∫ (1 - x)/(x - lnx)² dx
= x/(x - lnx) + C
-------------------------------------------------------------------------------------------------
∫ e^x (1 + sinx)/(1 + cosx) dx
= ∫ e^x/(1 + cosx) dx + ∫ e^x sinx/(1 + cosx) dx
= ∫ e^x/(1 + cosx) dx + ∫ sinx/(1 + cosx) d(e^x)
= ∫ e^x/(1 + cosx) dx + e^x sinx/(1 + cosx) - ∫ e^x * [cosx(1 + cosx) - sinx(-sinx)]/(1 + cosx)² dx
= ∫ e^x/(1 + cosx) dx + e^x sinx/(1 + cosx) - ∫ e^x/(1 + cosx) dx
= e^x sinx/(1 + cosx) + C
= e^x tan(x/2) + C
----------------------------------------------------------------------------------------
第三第四题是一样的?